2013
DOI: 10.1007/s00542-013-1753-8
|View full text |Cite
|
Sign up to set email alerts
|

RF MEMS switches fabrication by using SU-8 technology

Abstract: In this paper we present a novel process based on SU-8 technology for the fabrication of double clamped RF MEMS capacitive shunt switches in coplanar configuration. The key element of the exploited process is the MicroChem SU-8 2002 negative photoresist. The polymeric material is widely used in MEMS device processes because of its excellent thermal and chemical stability. In this paper, SU-8 polymer has been utilized in a double way to get suspended structures as double clamped beams: (i) SU-8 for the lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In this process, 150 °C instead of 300 °C for plated shower is used to make sure it will not affect the SU-8 layer. Next, around 7 μm thickness of polymer or any sacrificial layer such as SU-8 or polyimide is spin coated and cured up to 200 °C to form the anchor and sacrificial layer (Lucibello et al 2013). Adhesion between the sacrificial layer material and SU-8 is needed to be taken to account.…”
Section: Proposed Fabrication Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, 150 °C instead of 300 °C for plated shower is used to make sure it will not affect the SU-8 layer. Next, around 7 μm thickness of polymer or any sacrificial layer such as SU-8 or polyimide is spin coated and cured up to 200 °C to form the anchor and sacrificial layer (Lucibello et al 2013). Adhesion between the sacrificial layer material and SU-8 is needed to be taken to account.…”
Section: Proposed Fabrication Processmentioning
confidence: 99%
“…Recently, SU-8 was used as a passivation layer to elevate co-planar waveguide (CPW) for realising a low loss transmission line using low resistivity silicon wafer (ρ < 100 Ω cm). (Lucibello et al 2013;Marcelli et al 2008) had used SU-8 as a lateral support for RF MEMS switch and sacrificial layer. Our previous work reported that by depositing and patterning 25 µm thick SU-8 layer on a silicon substrate, the parasitic capacitance due to fringing field and loss of the varactor could be reduced, hence increasing the capacitance ratio and the Q-factor of the proposed RF MEMS varactor (Ramli et al 2016a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Imposing in Equation (21) the φ ihc value given by Equation (20), after some algebra, the following quadratic equation in the unknown U is obtained:…”
Section: The Double Cell Configurationmentioning
confidence: 99%
“…In [20] the authors have recently presented a novel process based on SU-8 for the fabrication of MEMS shunt capacitive devices. SU-8 is a negative photoresist, and has been used both for the lateral supports for the suspended membrane and as sacrificial layer.…”
Section: Characterization Of the Realized Mems Bridgementioning
confidence: 99%
See 1 more Smart Citation